Association between density of convenience and small grocery stores with diet quality in adults living in Mexico City: A cross sectional study - Rodríguez-Guerra, Ana Isabel; López-Olmedo, Nancy; Medina, Catalina; Hernández-Alcaraz, César; Ortega-Avila, Ana G.; Barquera, Simón (Frontiers in Public Health, 2022)
There is evidence of the association between different retail stores and food consumption, yet research is still limited in low- and medium-income countries, where the context of the food retail environment is different from that observed in high-income countries. Specifically, less is known about how convenience and small grocery stores, which offer products with immediate access, are associated with the diet as a whole. The present study assessed the association between density of convenience and small grocery stores and diet quality in adults from the Mexico City Representative Diabetes Survey 2015. A final sample size of 1,023 adults aged 20–69 years was analyzed. The density of stores was measured using Euclidean buffers within 500 meters of each participant's home. The Mexican Alternate Healthy Eating Index (MxAHEI) was used to assess diet quality. Multivariable Poisson models were used to test the association of convenience and small grocery stores densities with the MxAHEI. Although our results were not statistically significant, we observed a lower diet quality score among adults from Mexico City living in areas with a higher density of small grocery and convenience stores. More research is needed on the influence of environmental food retail on food consumption.